2005
DOI: 10.1577/a04-047.1
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of Refrigerated and Frozen Storage of Sperm of the Coppernose Bluegill

Abstract: The coppernose bluegill (CBG) Lepomis macrochirus purpurescens is a bluegill subspecies that is native to Florida. The CBGs and their hybrids are of interest as potential food fish. Our objectives were to (1) develop an osmolality activation curve for CBG sperm, (2) determine suitable cryoprotectants for the cryopreservation of CBG sperm, and (3) demonstrate the ability of cryopreserved CBG sperm to fertilize eggs. Sperm were stripped from mature CBGs (mean Ϯ SD ϭ 113 Ϯ 35 g, n ϭ 10), diluted in Hanks' balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Ca 21 -induced quiescence in bluegill sperm motility dilution of sperm into a hypoosmotic medium, tap water, was associated with the onset of motility. These results are consistent with the findings of Bates et al (2005), which demonstrated that the sperm of bluegill are quiescent in 265 mOsm/kg Hank's SIS but become motile in media of lower osmotic concentration. That sucrose inhibited motility similar to NaCl indicates that osmolality plays a primary role in maintaining sperm quiescent.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Ca 21 -induced quiescence in bluegill sperm motility dilution of sperm into a hypoosmotic medium, tap water, was associated with the onset of motility. These results are consistent with the findings of Bates et al (2005), which demonstrated that the sperm of bluegill are quiescent in 265 mOsm/kg Hank's SIS but become motile in media of lower osmotic concentration. That sucrose inhibited motility similar to NaCl indicates that osmolality plays a primary role in maintaining sperm quiescent.…”
Section: Discussionsupporting
confidence: 92%
“…This study is unique, however, in demonstrating that relatively low physiological levels of Ca 21 are inhibitory to bluegill sperm motility and contribute to the maintainence of quiescence of sperm in seminal plasma. Although the studies of Bates et al (2005) suggest that bluegill sperm are maintained quiescent by high osmolality, the SIS used in those studies contained 1.3 mmol/L Ca 21 , a level found inhibitory in conjunction with osmolality in this study. That Ca 21 is inhibitory to sperm motility is consistent with the findings of Okuno and Morisawa ('89), which showed motility of demembranated salmonid sperm is inhibited by 40.1 mmol/L Ca 21 .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Both chemicals function as intracellular cryoprotectants and are believed to achieve their cryoprotective abilities by decreasing the water content within the cells (McGann 1978). However, DMSO is generally more toxic to fish sperm than methanol at similar concentrations (Tiersch et al 2004a(Tiersch et al , 2004bBates et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Methanol permeates the sperm cell quickly to maintain the osmotic balance with the extracellular environment. It could be less toxic to fish sperm than dimethyl sulphoxide at similar concentrations (Tiersch, Wayman, Skapura, Neidig & Grier 2004;Bates, Williams, Lang & Tiersch 2005). Methanol has widespread use in cryopreservation application, in addition to its use in refrigerator storage to prolong the viability of sperm.…”
Section: Effect Of Inclusion Of Methanolmentioning
confidence: 99%